How to give exceptional customer service - Sealy, Stephen ([S.l.] : CareerTrack Publications, 1993)
The program is presented in four distinct tape volumes, each with a different theme. Volume 1 introduce to the power of exceptional service, volume 2 covers the essential skills of exceptional customer service, volume 3 focuses on how to please your most challenging customers, volume 4 wraps up the series with an array of advanced service skills
volume 1. The total service experience - volume 2. Delivering service with heart - volume 3. Pleasing the challenging customer - volume 4. Becoming a service star
Executive producer, Winsor White ; writers, Billy Reilly, Stephen Sealy, Jeff Salzman ; editors, Dale Hinkle, Mike Devereux
Host: Lisa Ford ; co-host: Terry Phillips
Keywords: Customer services